PROFESSIONAL LEARNING COMMUNITY MODEL FOR SCHOOL TEACHERS ADMINISTERED BY THE EDUCATION DEPARTMENT OF BANGKOK ARCHDIOCESE - Theresia Astanti Rorik Wahyudhanti; Nathara Mhunpiew; Michael Bistis (Sanata Dharma University Yogyakarta, 2026)
This study examined teachers’ perceptions of professional learning community (PLC) practices in schools administered by the Education Department of Bangkok Archdiocese (EDBA), developed a PLC model, and validated the proposed framework. An explanatory sequential mixed-methods design was used in three phases. In Phase 1, survey data from 351 teachers in five representative EDBA schools showed that all six PLC characteristics were perceived at a high level overall (x̄ = 4.31, SD = 0.548). However, item-level findings indicated less consistent areas in stakeholder participation, distributed leadership, depth of inquiry, evidence use, and supportive conditions. In Phase 2, semi-structured interviews with 21 participants from four representative EDBA schools explained these patterns, highlighting the influence of Catholic mission, leadership capacity, and structural constraints such as time, workload, trust, and limited resources. The integrated findings informed the PLC model development grounded in mission, collaboration, shared leadership, reflective growth, evidence use, and supportive structures. In Phase 3, a two-round Delphi process using the Context-Input-Process-Product (CIPP) framework validated the model as context-responsive, coherent, and feasible. The study recommends gradual implementation, stronger distributed leadership, protected time for collaboration, and a clear evaluation system to monitor PLC implementation across EDBA schools.